Efficacy Of Rivaroxaban Versus Warfarin For The Treatment Of Deep Vein Thrombosis At Tertiary Care Hospital, Islamabad - Yousaf, Mahnoor; Jalil, Aneza; Zafar, Maria; Sajjad, Zunaira; Nasir, Maham (Journal of Rawalpindi Medical College, 2025)
Objective: The occurrence of venous thromboembolism outside the pulmonary arteries or lower extremity conventional deep vein is referred to as deep vein thrombosis (DVT). The optimal anticoagulation treatment for deep vein thrombosis remained debatable. Therefore, the purpose of the current study was to compare Rivaroxaban versus Warfarin in treating deep vein thromboembolism at the Tertiary Care Hospital, Islamabad. Methods: A randomised controlled trial investigated 170 deep vein thrombosis (DVT) patients in the Department of Medicine, Pakistan Institute of Medical Sciences, Islamabad, from July 2023 to January 2024. Patients were categorised into two groups: Group R (Rivaroxaban) (N=85) and Group W (Warfarin) (N=85). Demographic data, such as age, gender, comorbidities, clinical outcomes, and efficacy recorded for both groups. Major bleeding included any fatal bleeding, bleeding in critical organs, or bleeding causing a haemoglobin drop ≥2 g/dL or requiring ≥2 units of blood transfusion. Minor bleeding is defined as overt bleeding, including events like mild epistaxis or bruising not requiring medical intervention. SPSS version 16 was used for statistical analysis. Results: The overall mean age of group R and W was 47.78±17.91 years and 46.45±18.01 years, respectively. Out of 170 patients, there were 83 (48.8%) males and 87 (51.2%) females. Gender based distribution of patients in both groups was as follows: Group R, N=85 (Male 42 (49.4%) and female 43 (50.6%) and Group W (Male 41 (48.2%) and female 44 (51.8%). Rivaroxaban (Group-R) showed higher efficacy, 72 (84.7%), than Warfarin (Group-W), 62 (72.9%). Conclusion: The present study observed that treatment with Rivaroxaban is preferred over Warfarin due to reduced risk of DVT, major bleeding, and minor bleeding.